Spatial and temporal variation of kelp forests and associated macroalgal assemblages along the Portuguese coast - Pinho, D. (2016)
Kelp communities are in decline in many regions. Detecting and addressing population declines require knowledge of patterns of spatial and temporal variation in the distribution and abundance of kelps and their associated organisms. We quantified kelp and associated macroalgal assemblages three times over a period of 2 years, at three regions along a natural gradient in temperature and nutrient availability across the Portuguese coast. Kelps were mostly found at the northern cool region (Viana do Castelo), which was also clearly separated from the two more southerly regions (Peniche, Sines) in terms of algal assemblage structure. This pattern was consistent, although varying in intensity, through time, providing support for this general spatial configuration. The overall richness of taxa increased towards lower latitudes. These findings indicated that kelp beds in southern Europe are currently restricted to northern Portugal, though supporting less diverse macroalgal assemblages compared with those located in central and southern Portugal.